(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article examines the role of education in the lives of aboriginal women, as represented in Follow the Rabbit-Proof Fence and Caprice: The Stockman’s Daughter written by Doris Pilkington within the theoretical frame work of Aileen Moreton Robinson whose writings reveal the double standards of the Australian government’s educational policies. In both the novels, there is representation of the Australian Law Reform Commission that was gradually introduced to each State and Territory along with their formal and extensive policies of protection during the late nineteenth and early twentieth century. These policies classified Aboriginal people in terms of race as full bloods, half-bloods, mixed bloods and half-castes. By denoting their aboriginal ancestry, the role of education is represented from the Aboriginal women’s perspective. This article analyses the experiences of Kate Muldune in Caprice: The Stockman’s Daughter, and Molly Craig Follow the Rabbit-Proof Fence who are coincidentally linked to the Moore River Native Settlement. Molly chose the way out from the Moore River Settlement never to return where as Kate chose freedom by staying there and getting educated. The representation is done as a framework that explores women experiences and perceptions of education which create a small opening for a new way of looking at the ingrained failure of the education system to serve and support aboriginal women.